Rosado Gamarra,Jeniffer Deyanira(2023)Efecto del regulador de crecimiento bencilaminopurina (BAP) en la propagación de Crasuláceas.Quevedo.UTEQ.77p. - Rosado Gamarra , Jeniffer Deyanira (2023)
Ecuador is a country with a very rich and varied flora, within this great variety are the Crassulaceae and its different genera, they are plants with great economic and commercial value, they present a very low percentage level in vegetative propagation. The objective of this research was to evaluate the effect of the growth regulator benzylaminopurine (BAP) on the propagation of Crassulaceae. Leaves from three Crassulaceae genera were used: Pachyveria, Echeveria and Sedum, selecting six leaves for each genus to which the BAP growth regulator was applied at different concentrations: 0, 500, 1000 and 1500. ppm for 3 repetitions, thus being 216 leaves, with a total of 12 treatments, at 31 days the data collection was carried out, a completely randomized design (DCA) was used, then the analysis of variance was carried out and the respective Tukey test at 95% probability. The results obtained showed that the Pachyveria genus in the concentration of 500ppm demonstrated to obtain a greater efficacy in terms of the variables number of roots, root volume, root diameter, root area and root length, likewise the Pachyveria genus in doses of 500ppm was the one that showed to obtain the best response in the variables of sprout diameter and quantity of sprout, increasing the greatest amount of propagation, the results obtained show that the application of the BAP growth regulator has the capacity to promote vegetative propagation in Crassulaceae species.